Tuning the Redox Properties of a Nonheme Iron(III)–Peroxo Complex Binding Redox-Inactive Zinc Ions by Water Molecules - Lee, Yong-Min (Chemistry, 2015)
Redox-inactive metal ions play important roles in tuning chemical properties of metal–oxygen intermediates. Herein we report the effect of water molecules on the redox properties of a nonheme iron(III)–peroxo complex binding redox-inactive metal ions. The coordination of two water molecules to a Zn(2+) ion in (TMC)Fe(III)-(O(2))-Zn(CF(3)SO(3))(2) (1-Zn(2+)) decreases the Lewis acidity of the Zn(2+) ion, resulting in the decrease of the one-electron oxidation and reduction potentials of 1-Zn(2+). This further changes the reactivities of 1-Zn(2+) in oxidation and reduction reactions; no reaction occurred upon addition of an oxidant (e.g., cerium(IV) ammonium nitrate (CAN)) to 1-Zn(2+), whereas 1-Zn(2+) coordinating two water molecules, (TMC)Fe(III)-(O(2))-Zn(CF(3)SO(3))(2)-(OH(2))(2) [1-Zn(2+)-(OH(2))(2)], releases the O(2) unit in the oxidation reaction. In the reduction reactions, 1-Zn(2+) was converted to its corresponding iron(IV)–oxo species upon addition of a reductant (e.g., a ferrocene derivative), whereas such a reaction occurred at a much slower rate in the case of 1-Zn(2+)-(OH(2))(2). The present results provide the first biomimetic example showing that water molecules at the active sites of metalloenzymes may participate in tuning the redox properties of metal–oxygen intermediates.